Report of a Case of Radiation-Induced New-Onset Vitiligo with Collective Review of Cases in the Literature of Radiation-Related Vitiligo. (5th August 2013) - Pavithran, Keechilat; Pande, Shripad Brahmanand; Dinesh, Makuny
Abstract : Radiation-induced hypopigmentation consistent vitiligo has been reported in a few case reports. We report herewith a case of vitiligo at the site of radiation delivery after a lag of several months in a patient with preexisting hypothyroidism without a previous or family history of vitiligo, and review the cases reported in the literature collectively.